Effects of Varenicline, Depressive Symptoms, and Region of Enrollment on Smoking Cessation in Depressed Smokers - Doran, Neal (Nicotine Tob Res, 2018)
INTRODUCTION: Despite effective treatments, relapse to smoking remains a vexing global health problem. One predictor of relapse is depressive symptoms. Medications such as varenicline reduce withdrawal-related symptoms of depression, reducing relapse. This study examined whether varenicline moderated the effect of depressive symptoms on relapse, and whether this varied by region of enrollment. METHODS: Adult smokers (n = 525; 37% male) with past or current, stable major depressive disorder recruited from United States (n = 255), and European (n = 270) sites participated in a randomized, double-blind cessation treatment trial including 12 weeks of varenicline or placebo, with 40-week nontreatment follow-up. RESULTS: Longitudinal and binary logistic regressions were used to model the probability of sustained abstinence by end of treatment and point-prevalence abstinence in follow-up. The association between depression symptoms and abstinence was moderated by intervention group at end of treatment, and by region during follow-up: more severe symptoms were associated with end-of-treatment relapse for placebo (odds ratio [OR] = 0.91, p = .003), but not varenicline (OR = 0.99, p = .568). During follow-up, increased symptoms of depression predicted greater likelihood of smoking for European (p = .009) but not US participants. Europeans were more likely to be abstinent for both outcomes (p < .01). CONCLUSIONS: These results extend studies demonstrating varenicline is associated with less withdrawal-related depression, and suggest it aids cessation even in smokers with depressive symptoms. Findings also suggest regional differences in the relationship between depressive symptoms and cessation that may be related to differences in prevalence. IMPLICATIONS: This study indicates varenicline may aid cessation partially by reducing withdrawal-related symptoms of depression. It also suggests that the impact of depressive symptoms on cessation varies regionally, and that this variation may be related to differences in smoking prevalence.